LEGAL STATUS AND COST-EFFECTIVENESS OF SUPERVISORY BODIES IN PREVENTING OFFENSES IN THE CONSTRUCTION SECTOR - Volodymyr Buha; Valentyn Tulinov; Valerii Kosse (Baltic Journal of Economic Studies)
The purpose of the present article is to analyse the legal status and cost-effectiveness of supervisory bodies in preventing violations in the construction sector. Methodology. The present study employed a range of general scientific methods of formal logic (analysis, synthesis, deduction, induction, analogy, abstraction and modelling) as well as a number of special methods (a logico-legal method and an axiomatic method). The employment of these methods enabled the disclosure of the legal status of supervisory bodies in the prevention of offences in the field of construction. Results. The development of the country's economy is closely connected with the following main sectors: industry, agriculture, transport and communications, construction, education, and other spheres. It is imperative to acknowledge the inherent interconnectedness that characterises all components of the economy. The dynamic interplay amongst these elements serves as the crux that determines the strategic direction of both individual sectors and the economy in its entirety. The coordination of activities across different sectors, and the degree to which these sectors influence one another, directly impact the overall efficiency of economic growth. The construction industry, specifically, assumes a pivotal function, with a concentration on new construction, reconstruction, and the augmentation of production capacity in associated sectors. Conversely, such industry is contingent on the products and services of other sectors of the economy. In the contemporary context of Ukraine's economic development, a particular emphasis is placed on strategic planning. This facilitates the formulation of effective plans and the adaptation of tasks in response to changes and features in the processes of development and co-operation across various economic sectors. In the aftermath of the imposition of martial law in Ukraine, a moratorium on inspections has been declared. Accordingly, the Resolution of the Cabinet of Ministers of Ukraine No. 303 dated March 13, 2022, entitled "On Termination of Measures of State Supervision (Control) under Martial Law", has effectively suspended all scheduled and unscheduled measures of state supervision (control) and state market supervision for the duration of martial law, as initially established by the Decree of the President of Ukraine "On Introduction of Martial Law in Ukraine" No. 64 dated February 24, 2022. The moratorium is applicable to a range of measures, including those pertaining to state architectural and construction control. This enables unscrupulous developers to undertake construction works that do not comply with the legislative and state building regulations, or to carry out such works without the requisite documentation. Nevertheless, as outlined in paragraph 2 of the Resolution, the implementation of unscheduled measures of state supervision (control) on the basis of decisions made by central executive bodies, which are intended to ensure the formation of state policy in the relevant areas, is permitted under conditions of martial law, provided that there is a threat that has a negative impact on the rights, legitimate interests, life and health of an individual, the protection of the natural environment and the security of the state, as well as the observation of international obligations of Ukraine. In the above circumstances, the state architectural and construction control body may apply to the central body responsible for formulating state policy in the field of construction and urban development (currently the Ministry of Community, Territories and Infrastructure Development of Ukraine) for permission to carry out an inspection. Practical implications. In accordance with the legal status of supervisory bodies in preventing offences in the field of construction, such activity is defined as an administrative and preventive procedure. Furthermore, it can be both disputed (i.e., conflict) and undisputed (i.e., non-conflict). Additionally, it can be regarded as administrative and organisational, as well as interventional (initiated by a public entity). At present, a trend is being observed in the country that is both understandable and justifiable. This trend involves the delegation of powers in relation to state architectural and construction control to local self-government bodies. The cost-effectiveness of supervisory bodies in preventing violations in construction is a crucial factor for the stability and development of the construction market. The implementation of rigorous supervision protocols has been demonstrated to result in a substantial reduction in violations, thereby mitigating substantial economic expenditures. This, in turn, fosters the creation of a secure environment conducive to the advancement of construction, which is recognised as the cornerstone for achieving sustainable economic growth within the nation. The legal status and effectiveness of supervisory bodies in preventing violations in the construction sector are important aspects for ensuring safety, quality and compliance with standards in this sphere. The significance of effective oversight by state entities in the construction sector is profound, given its direct impact on the social and economic well-being of the nation, the quality of life of its citizens, and environmental safety.